The role of economic courts in the economic development of Ukraine - Бакаянова, Нана Мезенівна; Бакаянова, Н. М.; Bakaianova, Nana M.; Цісельський, Олег Володимирович; Tsiselskyi, Oleh V. (Baltic Journal of Economic Studies, 2022)
The subject of the study is the role of economic courts in the economic development of Ukraine. The purpose of the article is determined by the current economic processes taking place in the country in connection with the full-scale aggression of the Russian Federation and the introduction of martial law in the territory of the state by the Decree of the President of Ukraine of February 24, 2022. According to preliminary forecasts, by the end of 2022 inflation in the country will increase to over 30%, and by the end of 2023 and 2024 it is expected to reach 20.7% and 9.4% respectively. Therefore, the purpose of the article is to provide a theoretical and practical substantiation of the impact of economic courts on the support and development of the State's economy in modern conditions. The methodological basis of the work is a set of general philosophical, general scientific and logical methods, the combination of which allowed to achieve a certain level of objectivity, comprehensiveness, as well as the validity of the study and the reliability of the conclusions. The leading role in the work is played by the statistical method, which made it possible to outline the trends in the number of considered economic cases, the amount of property claims of plaintiffs and the amount of funds allocated for recovery (indicators for 2021, 2020, 2019, 2018, etc. were considered). The results of the study make it possible to conclude that the influence of economic courts is both direct and indirect. Direct influence is manifested in the results of administration of justice, resolution of commercial disputes and satisfaction of interests of business entities. The indirect impact is related to the replenishment of the special fund of the State Budget of Ukraine by economic courts through the receipt of court fees. In addition, the difficulties faced by judges of economic courts in the context of the full-scale aggression of the Russian Federation against Ukraine are highlighted: 1) the danger to the life and health of judges, court staff and visitors to the court in general (for example, in Odesa from February 24, 2022 to September 8, 2022, air alert was announced fifty-one times, its total duration was thirty-nine hours); 2) destruction or damage to the material and technical base of economic courts (for example, in the Economic Court of Donetsk region and the Economic Court of Luhansk region, located in the same building, the plaster on the facade of the building was damaged, the building of the Economic Court of Mykolaiv region was damaged); 3) lack of judges (this is due to the suspension of the work of the High Qualification Commission of Judges of Ukraine, on the one hand, and the fact that some judges left the country with the beginning of hostilities); 4) insufficient level of funding (in 2020, the Supreme Court received six appeals from economic courts regarding insufficient funding, and in 2021, special attention was paid to the problem of underfunding of the Economic Court of Kyiv region, which led to a shortage of funds in the wage fund of the court staff). Practical implications. It is determined that any further actions of the state should be aimed at raising the qualification level of judges of economic courts and public confidence in them, popularization of the procedure for applying to economic courts and legal proceedings. Value/originality. The study confirms the effectiveness of economic courts and allows to analyze it from a new perspective, since, as most scientific studies show, the effectiveness of economic courts is mainly associated with: the speed of consideration of cases; a small number of decisions appealed to a higher instance (compared to the indicators of general and administrative courts); the percentage of cases considered. Предметом дослідження є роль господарських судів в економічному розвитку України. Мета статті зумовлена ​​поточними економічними процесами, що відбуваються в країні у зв’язку з повномасштабною агресією Російської Федерації та введенням на території держави воєнного стану Указом Президента України від 24 лютого 2022 року. За попередніми прогнозами, на кінець 2022 року інфляція в країні зросте до понад 30%, а на кінець 2023 та 2024 років – очікується, що становитиме 20,7% і 9,4% відповідно. Тому метою статті є теоретичне та практичне обґрунтування впливу господарських судів на підтримку та розвиток економіки держави в сучасних умовах. Методологічною основою роботи є сукупність загальнофілософських, загальнонаукових та логічних методів, поєднання яких дозволило досягти певного рівня об’єктивності, всебічності, а також обґрунтованості дослідження та достовірності висновків. Провідну роль у роботі відіграє статистичний метод, який дав змогу окреслити тенденції щодо кількості розглянутих господарських справ, розміру майнових вимог позивачів та обсягу коштів, спрямованих на стягнення (розглянуто показники за 2021, 2020, 2019, 2018 роки тощо). Результати дослідження дають змогу зробити висновок, що вплив господарських судів є як прямим, так і опосередкованим. Прямий вплив виявляється в результатах здійснення правосуддя, вирішення господарських спорів та задоволення інтересів суб'єктів господарювання. Опосередкований вплив пов’язаний з поповненням господарськими судами спеціального фонду Державного бюджету України за рахунок надходження судового збору. Крім того, висвітлено труднощі, з якими стикаються судді господарських судів в умовах повномасштабної агресії Російської Федерації проти України: 1) загроза життю та здоров’ю суддів, працівників суду та відвідувачів суду загалом (наприклад, в Одесі з 24.02.2022 по 08.09.2022 повітряна тривога оголошувалася 51 раз, загальна тривалість – 39 годин); 2) знищення або пошкодження матеріально-технічної бази господарських судів (наприклад, у господарському суді Донецької області та господарському суді Луганської області, розташованих в одній будівлі, пошкоджено штукатурку на фасаді будівлі, пошкоджено будівлю господарського суду Миколаївської області); 3) нестача суддів (це пов’язано з призупиненням роботи Вищої кваліфікаційної комісії суддів України, з одного боку, та тим, що частина суддів виїхала з країни з початком бойових дій); 4) недостатній рівень фінансування (у 2020 році до Верховного Суду надійшло шість звернень господарських судів щодо недостатнього фінансування, а у 2021 році особливу увагу приділено проблемі недофінансування Господарського суду Київської області, що призвело до дефіциту коштів у фонді оплати праці працівників апарату суду). Практичні наслідки. Визначено, що будь-які подальші дії держави мають бути спрямовані на підвищення кваліфікаційного рівня суддів господарських судів та довіри до них громадян, популяризацію порядку звернення до господарських судів та судочинства. Цінність/оригінальність. Дослідження підтверджує ефективність господарських судів та дозволяє проаналізувати її під новим кутом зору, оскільки, як свідчить більшість наукових досліджень, ефективність господарських судів в основному пов’язана зі: швидкістю розгляду справ; мала кількість оскаржених рішень до вищої інстанції (порівняно з показниками загальних та адміністративних судів); відсоток розглянутих справ.
Bakayanova N. The role of economic courts in the economic development of Ukraine / N. Bakayanova, O. Tsiselskyi // Baltic Journal of Economic Studies. - 2022. - Vol. 8, No. 3. - P. 14-19. Режим доступу: https://doi.org/10.30525/2256-0742/2022-8-3-14-19
Keywords: commercial (economic) courts; judicial system; economics; entrepreneurship; господарські (господарські) суди; судоустрій; економіка; підприємництво